Contrasting effects of two Acacia species on understorey growth in a drylands environment: interplay of canopy shading and litter interference. (28th November 2017) - Helman, David; Leu, Stefan; Mussery, Amir
Abstract: Questions: Do tree species with similar canopy structures but distinct litter production volumes affect the understorey growth in dryland environments differently? How does rainfall impact the magnitude and sign of these effects? Location: Woodland savanna, northern Negev drylands, Israel. Methods: We determined understorey herbaceous productivity beneath the canopy of two N‐fixing tree species ( Acacia victoriae and Acacia salicina ) with comparable canopy structures (canopy height and area) but distinct litter production volumes. Biomass was measured beneath A. victoriae trees and in the open area between the trees for 7 yrs and beneath A. salicina and the nearby open area for 2 yrs. Light measurements, litter biomass, fine root density and nutrients and gravimetric water content in the top soil were assessed for both species. Annual rainfall and the coefficient of variation in daily rain were used to determine rainfall effects on tree–grass relations. Results: Acacia victoriae and A. salicina had contrasting positive and negative effects on understorey growth, respectively. Both species had comparable fine root densities, soil moisture and nutrient content beneath their canopies, with a higher soil water content than the open area. The large amount of leaf litter produced by A. salicina appeared to suppress the understorey growth, likely via light interference at the soil surface, which outweighed the positive effect of moisture conditions. Acacia victoriae that produced significantly lesser amounts of litter facilitated the understorey growth via canopy shading (likely through reducing evaporative loss). Both the rainfall amount and its intra‐annual variability reduced the magnitude of the tree effect but did not change its sign. Conclusions: Tree leaf litter production may have a contrasting effect on understorey growth, ranging from positive to negative even in the same environment. Changes in rainfall amount and intra‐annual rainfall variability affect the magnitude of the effect but not its sign. Abstract : Tree‐grass interactions change from competition to facilitation across water availability gradients depending on the N‐fixing capacity of the trees. We found that two similarly N‐fixing tree species had contrasting effects on understorey growth because of differing litter production rates. Understorey growth was suppressed via light interference in the more litter‐productive trees. Our results have important implications for the stress‐gradient hypothesis.View of Acacia salicina (left) and Acacia victoriae (right) trees and their contrasting effects on understorey growth (Photo credit: D. Helman).